Predicting Lake Ice Decay. - Ashton,George D (1983)
A nine-year record of the lake ice decay pattern of Post Pond in Lyme, New Hampshire, is analyzed using a simple algorithm. Quite good correlations between decay rates and thawing degree-days are obtained using heat transfer coefficients on the order of 15-20 W/sq. m./deg C. (Author)